2019
DOI: 10.7717/peerj.7357
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and poor quality of life are significantly associated with suicidal ideation of senior high school students in Chongqing, China

Abstract: Background Adolescence is a vulnerable period of life, and many mental health and behavioral problems emerge during this particular period, including depression, internet addiction (IA), and suicidal behaviors. Poor quality of life (QOL) and IA have been found to be significantly associated with suicidal ideation (SI) among Chinese university students, of whom most have been adults. Nevertheless, their associations with SI are rarely studied among Chinese adolescents. The objective of this study was to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
2
14
1
2
Order By: Relevance
“…Pretest were carried out to check the suitability and understandability of the questionnaires and functionality of the website. Online psychological assessments had been adopted to adolescent depression or suicide screening in in our groups previous researches [ 24 ]. The test time was set by pretest results, and questionnaires with a test duration of less than 180 s were deleted.…”
Section: Methodsmentioning
confidence: 99%
“…Pretest were carried out to check the suitability and understandability of the questionnaires and functionality of the website. Online psychological assessments had been adopted to adolescent depression or suicide screening in in our groups previous researches [ 24 ]. The test time was set by pretest results, and questionnaires with a test duration of less than 180 s were deleted.…”
Section: Methodsmentioning
confidence: 99%
“…Students were asked to select one response option to a 5-point Likert scale from "not at all" to "always". The scores for all 20 items were summed (therefore from 20 to 100), and a total score of 50 or beyond meant a presence of the Internet addiction behavior [12,28]. The reliability and validity of YIAT-C have been established in Chinese children [12], and in the present study, the Cronbach's alpha was 0.921.…”
Section: Internet Addictionmentioning
confidence: 61%
“…Accompanying the increased internet and computer use, Internet addiction has increasingly recognized as a serious, worldwide public health concern in recent decades. Recent evidence suggested that Internet addiction could contribute to psychiatric symptoms and behavioral problems, such as substance use disorder, attention-de cit hyperactivity disorder, social anxiety disorder, and suicidal attempts [11,12]. Moreover, the majority of LBC live with old-age grandparents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 10-20% of children and adolescents suffer from mental disorders, with half of all them starting by the age of 14 and three-quarters before the age of 25 [3]. In young adults, mental health conditions can present as lack of confidence, body image issues, social isolation, poor performance in academia, internet addiction and poor quality of life [4]. Self-harm and suicidal behaviour in adolescence are markers of mental health disorders and represent unfavourable social outcomes in young adulthood, mostly accounted for by adolescent psychosocial problems [5].…”
Section: Discussionmentioning
confidence: 99%